Landasan Berfikir Filsafat Pendidikan Islam - Asril, Zainal; Mardiana, Puja Dikusuma; Febriani, Afifah; Mardi, Anton; Pratama, Andra; Saputra, Ahmad; Nurhaliza, Pioni (LP2M STAI Balaiselasa YPPTI Pesisir Selatan Sumatera Barat, 2025)
Islamic educational philosophy is a branch of knowledge that discusses the concepts, principles, and objectives of education based on Islamic teachings. This article examines how philosophical thinking in the context of Islamic education can help us understand the essence of education as a process of forming perfect human beings in harmony with divine and human values. This philosophical approach explores fundamental issues such as the purpose of education, the concept of humanity, the role of teachers, teaching methods, and the relevance of knowledge from an Islamic perspective. Using conceptual analysis and textual hermeneutics, this research demonstrates that Islamic educational philosophy emphasizes a balance between intellectual, emotional, and physical education, as well as the importance of integrating religious and secular knowledge. This article is expected to serve as a foundation for the development of an educational system that is relevant to the needs of Muslims in the modern era, without neglecting the underlying theological principles.